Efektifitas Bentuk Huruf Medium Leaflet dalam Meningkatkan Pengetahuan Petani Jagung di Kelurahan Rahandouna Kecamatan Poasia Kota Kendari - Isnian, Sitti Nur; Buana, Tjandra; Putri, Risya Septiani Rezky (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
This study departs from the phenomenon of the presence of downy mildew disease in corn farming by corn farmers in Rahandouna Village, Poasia District, Kendari City, Southeast Sulawesi. Control efforts have been made in the last 3 years through increasing farmers' knowledge by utilizing the medium leaflet, but the downy mildew is still a problem that results in the production of corn which is not optimal. In-depth research is needed to ensure the effectiveness of the leaflet medium used to increase farmers' knowledge. Therefore this study aims to reveal the effectiveness of the leaflet medium in increasing farmers' knowledge and to strive to improve its effectiveness by focusing on the design of the letters. The research was conducted in Rahandouna Sub-District, Poasia District, Kendari City, which was conducted for 1 month, January 2020, with 36 respondents. The research was designed as an experimental study with pre-post-test treatment. The results of the study which were calculated through the effective formula using the t-test showed that the leaflet medium was effective in increasing farmers' knowledge with an effective value of 65.29%, with the design of an upright letter shape. It is hoped that the leaflets produced from this research can effectively increase farmers' knowledge so that the downy mildew disease can be controlled.